ASCORBIC ACIDS CONTENTS IN COMMERCIAL JUICES AND BEVERAGES - Maryam, B.; Rafique, R.; Quratulain, Miss.; Mashiatullah, A.; Sultana, T.; Javed, T. (The Nucleus, 2012)
Vitamin C is water soluble which is essential for many physiological processes. Humans cannot synthesize vitamin C, so it must be taken through diet or as food supplement. Nowadays many liquid juices available in the market claim high levels of vitamin C. The present study was designed to check levels of vitamin C in commercially available juices and to verify manufacturers claim of vitamin C addition. Twenty five (25) juices, beverages, solid soft drinks of various brands were purchased from five locations in Islamabad and their ascorbic acid content was determined by Polarography. Juices were categorized into four groups namely international companies, Pakistani companies of good repute, other local companies, and solids drinks/ vitamin C supplement tablets. Results showed that measured and reported values of vitamin C in some international brand juices are comparable while others are not. Most of the reputed companies of Pakistan origin did not have any vitamin C in their products or their amount was negligible when compared with the reported values. Overall vitamin C was below detectable limit in juice packs of local companies. Vitamin C concentration in vitamin C tablets and solid soft drinks is comparable with reported values. On the basis of this study it is suggested that local companies may be using some chemical to develop taste and flavor of vitamin C in their products. It is recommended that strict quality control be implemented at the factories to prepare such products with correct amounts of vitamin C.